The Dynamics of Sanskritising and Vernacularising Practices in the Social Life of the Bhāgavata Purāṇa. (21st August 2018) - Holdrege, Barbara A
Abstract: The Bhāgavata Purāṇa gives expression to a new type of aesthetic, passionate, and ecstatic Kṛṣṇa bhakti that is rooted in the vernacular Tamil devotional traditions of the Āḻvārs supported by the popular power matrix. The processes of Sanskritisation and vedacisation served as a means of legitimating and promulgating the Bhāgavata's innovative devotional teachings by incorporating them within a Sanskritic framework invested with the pan-Indian canonical authority of a vedacised Purāṇa. Through this strategic appropriation of the discursive practices of Sanskritisation and vedacisation, the exponents of Kṛṣṇa bhakti sought to position their devotional teachings in relation to the dominant discourse of the brahmanical elite, while at the same time they developed countervailing vernacularising practices through which they sought to reclaim the Bhāgavata Purāṇa for the popular power matrix from which its devotional teachings originally derived. In this article, I interrogate the mechanisms of 'scripturalising' at work in the social life of the Bhāgavata Purāṇa, which involve a complex interplay between the dynamics of Sanskritising and vedacising practices, on the one hand, and vernacularising practices, on the other, through which we move from the world of the text to the text-in-the-world.